2002
DOI: 10.1021/ja020253n
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Behavior of 2:1 Inclusion Complexes of Cyclodextrins and Charged Porphyrins in Aqueous Organic Media

Abstract: Two heptakis(2,3,6-tri-O-methyl)-beta-cyclodextrin (TMe-beta-CD) molecules strongly include the peripheral substituents at the 5- and 15-positions of the charged meso-tetrasubstituted porphyrins, PorSub(4) [TPPS(4) (Sub = p-C(6)H(4)-SO(3)(-)), TPPOC3PS (p-C(6)H(4)-O-(CH(2))(3)-p-C(6)H(4)-SO(3)(-)), TCPP (Sub = p-C(6)H(4)-CO(2)(-)), and TPPOC3Py (p-C(6)H(4)-O-(CH(2))(3)-Py(+)Br(-)), where Py(+) = N-alkylpyridinium] in aqueous ethylene glycol. The binding constants (K(1) and K(2)) and the rate constants (k(1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
184
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 197 publications
(200 citation statements)
references
References 40 publications
13
184
0
Order By: Relevance
“…Per-O-methylated CD derivatives strongly interact with anionic porphyrins such as meso-tetrakis(4-sulfonatophenyl)-porphyrin (TPPS) to form 2 : 1 inclusion complexes in aqueous solution. [19][20][21] In 1996, Kano et al first reported the 1 : 2 inclusion complex of TPPS with 2,3,6-tri-O-methyl-β-cyclodextrin (TMe-β-CD, Fig. 2).…”
Section: Porphyrin-cyclodextrin (Cd) Supramolecular Complexesmentioning
confidence: 99%
“…Per-O-methylated CD derivatives strongly interact with anionic porphyrins such as meso-tetrakis(4-sulfonatophenyl)-porphyrin (TPPS) to form 2 : 1 inclusion complexes in aqueous solution. [19][20][21] In 1996, Kano et al first reported the 1 : 2 inclusion complex of TPPS with 2,3,6-tri-O-methyl-β-cyclodextrin (TMe-β-CD, Fig. 2).…”
Section: Porphyrin-cyclodextrin (Cd) Supramolecular Complexesmentioning
confidence: 99%
“…rate constants between TPPS4 and β-CD in ethylene glycol-H2O (3:1) was previously reported). 56,57 The free-base TPPS4 was immediately incorporated by β-CD in aqueous solution to form the inclusion complex, TPPS4-(β-CD)2. The solubility of β-CD in water is lower than that of other CD (cf.…”
Section: Acceleration Mechanismmentioning
confidence: 99%
“…The most important feature of such cyclic structures is a hydrophobic inner cavity and a hydrophilic outer surface, hence their ability to form non-covalent inclusion complexes with organic [34], inorganic [35], biological molecules [36] or supramolecular aggregates [37,38]. The main factors acting as driving force to form host-guest complexes and their stabilities are hydrophobic forces, the sizes of molecules/cavity and the guest properties.…”
Section: Introductionmentioning
confidence: 99%